Caring for Intersubjective Relationships. : A Phenomenological-Existential Approach in Heterogeneous School Contexts - Papa, Irene (Studi sulla Formazione/Open Journal of Education, 2024)
The contribution proposes some reflections on the design of an educational experience aimed at upper secondary schools and concerned with the care of intersubjective relationships. Starting with some observations on the current condition of youth, and illustrating the theoretical foundations that shaped the classroom practice, the essay offers a description of the activity, focusing in particular on the ethical-political value of the experience.